The Influence of Organizational Culture and Employee Commitment on Employee Performance with Job Satisfaction as a Mediating Variable at PT. Bumi Menara Internusa, Kwanyar Branch - Irsyadul Ibad; Anugrahini Irawati (Universitas Trunojoyo Madura, 2026)
Purpose: This study aims to analyze the influence of organizational culture and employee commitment on employee performance, explicitly evaluating the pivotal role of job satisfaction as an intervening variable at PT. Bumi Menara Internusa, Kwanyar Branch. Design/methodology/approach: Employing a quantitative research method, data collection was conducted via structured questionnaires distributed to participants. Random sampling was utilized in this study, resulting in a final sample size of 75 respondents. Data analysis was systematically performed using multiple linear regression tests within SPSS 25 software. Findings: The empirical results indicate that organizational culture and employee commitment do not directly impact employee performance. However, job satisfaction significantly affects employee performance. Furthermore, job satisfaction significantly alters the influence of organizational culture on employee performance, whereas it does not significantly change the impact of employee commitment on employee performance. Research limitations/implications: The primary limitation stems from the narrow sample scope of 75 participants restricted to a single regional branch. Future research should extend this framework across broader geographical regions and multiple industry sectors to verify the generalizability of these findings. Practical implications: Practitioners and entrepreneurs should prioritize enhancing direct job satisfaction elements rather than relying solely on abstract corporate culture or baseline employee commitment, as satisfaction serves as the primary mechanism driving worker performance and organizational transformation. Originality/value: This study provides valuable empirical insights into human resource dynamics by demonstrating that job satisfaction functions as an essential, foundational catalyst required to activate performance within manufacturing environments